(untitled) (Bangladesh Journal of Agricultural Research, 2011)
An experiment was conducted at Mouchack textile industrial area of Gazipur for two consecutive years (1999-2000) to study the effects of use of industrial waste water on the yield, nutrient content, and uptake of Boro rice. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The six treatments in this study were: T1: uncontaminated field + fresh water, T2: uncontaminated field + mixed water, T3: uncontaminated field + contaminated water for non-contaminated field, and T4: effluent contaminated field + fresh water, T5: effluent contaminated field + mixed water, T6: effluent contaminated field + contaminated water for contaminated field. Among the six treatments, uncontaminated field + fresh water (T1) showed the best positive effect on rice. The N, P. K, and S contents and uptake were higher in T1, but Zn, Mn, Fe, Cu, and Pb were higher in T6 treatment. The treatment T1, gave the highest grain yield (5.23 t/ha in 1999 and 5.40 t/ha in 2000), followed by mixed water (4.19 t/ha in 1999 and 4.24 t/ha in 2000) in both the growing seasons. Keywords: Industrial waste water; heavy metal; textile waste water; yield; nutrient content; uptake; rice. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9260 BJAR 2011; 36(2): 319-331